Analysis of Trade and Economic Relations of the Russian Federation with the Countries of the Commonwealth of Independent States - Nadezhda Petrovna Volovik (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The CIS member states are our nearest neighbors and traditionally have been principal trade partners of the Russian Federation. In the course of political and economic changes developing in the CIS member states new features and trends appear in the development of trade relations of these countries, problems and challenges of restoration of traditional and search for new forms of trade links. Developing changes require constant investigation of current event with the aim of defining the prospects of trade and economic cooperation, development of proposals for its upgrading, search for way to solve the issues. All this determines the thematic justification. The research focuses on trade and economic cooperation of the Russian Federation with CIS member states. The objective of the research is to develop proposals on measures and directions for deepening integration processes in the CIS. In accordance with the intended objective analysis of current state of trade and economic cooperation of the Russian Federation with the CIS member states was carried out. In order to assess integration processes on the micro level, integration indices of merchandise trade were measured: importance factors of mutual trade flows, level of openness of the CIS economies regarding the Russian Federation, Grubel - Lloyd Index which allows to measure the level of intraindustry trade of Russia with the CIS member states. Conducted analyses demonstrated that the CIS member states are lacking developed intraindustry cooperation links which are the basis of integration process. The CIS member states complement each other on the intra-industry level which reflects in the structure of mutual trade. Dominance of fuel and resource goods, which strongly depend on the global market conditions, in the Russian trade turnover with the CIS member states does not lead to close links between national economies. By applying complex analyses method of the current state of trade and economic cooperation between the RF and the CIS member states principal directions of improvement of interstate economic cooperation were determined.